Anuario musical - Frenk, Margit (El Colegio de México, 2007)
Se reseñó: Anuario musicalTomo 1 (1946), Tomo 2 (1947), Tomo 3 (1948), Tomo 4 (1949), Tomo 5 (1950),Tomos 6 (1951) y 7 (1952) y Tomo 8 (1953).